Evaluation of Porous (Poly(lactide-co-glycolide)-co-(ε-caprolactone)) Polyurethane for Use in Orthopedic Scaffolds - Gaëlle Savin; Océane Sastourne-Array; Sylvain Caillol; Audrey Bethry; Michel Assor; Ghislain David; Benjamin Nottelet (Molecules, 2024)
To develop an orthopedic scaffold that could overcome the limitations of implants used in clinics, we designed poly(ester-urethane) foams and compared their properties with those of a commercial gold standard. A degradable poly(ester-urethane) was synthetized by polyaddition between a diisocyanate poly(ε-caprolactone) prepolymer (PCL di-NCO, Mn = 2400 g·mol−1) and poly(lactic-co-glycolic acid) diol (PLGA, Mn = 2200 g·mol−1) acting as a chain extender. The resulting high-molecular-weight poly(ester-urethane) (PEU, Mn = 87,000 g·mol−1) was obtained and thoroughly characterized by NMR, FTIR and SEC-MALS. The porous scaffolds were then processed using the solvent casting (SC)/particle leaching (PL) method with different NaCl crystal concentrations. The morphology, pore size and porosity of the foams were evaluated using SEM, showing interconnected pores with a uniform size of around 150 µm. The mechanical properties of the scaffolds are close to those of the human meniscus (Ey = 0.5~1 MPa). Their degradation under accelerated conditions confirms that incorporating PLGA into the scaffolds greatly accelerates their degradation rate compared to the gold-standard implant. Finally, a cytotoxicity study confirmed the absence of the cytotoxicity of the PEU, with a 90% viability of the L929 cells. These results suggest that degradable porous PLGA/PCL poly(ester-urethane) has potential in the development of meniscal implants.